Clinical study of stent forming for symptomatic internal carotid artery stenosis - Zhang, Yiqin (Medicine (Baltimore), 2020)
Stroke is one of the diseases that seriously threaten the survival and health of human beings. In Europe and the United States, stroke is the second leading cause of death after heart disease and tumors.([1]) Stroke is also one of the fatal diseases in Asian countries. On average, about 1.5 million new stroke patients are added each year in China, and the incidence of stroke is increasing year by year. About 80% of all stroke patients are ischemic stroke, and symptomatic internal carotid atherosclerotic stenosis is another important cause of ischemic stroke. Ipsilateral carotid stenosis ≥50% increases the incidence of transient cerebral ischemia and stroke in the carotid artery region by 10% to 15%, and is also closely related to the recurrence of acute and long-term stroke in patients.([2]) Therefore, the clinical application and efficacy of carotid stenting in patients with symptomatic internal carotid artery stenosis are analyzed and evaluated to provide a basis for the selection of clinical treatment options. The clinical data of patients with symptomatic carotid stenosis who underwent carotid stenting and the clinical data of conservative treatment of patients with symptomatic carotid stenosis were retrospectively analyzed, and the carotid stenosis rate, symptoms, and National Institute of Health stroke scale where compared before and after surgery. And activities of daily living score. Because the control group treatment method in this article is completely free for patients to choose, and belongs to a retrospective analysis, the results suggest that it can provide a high-quality treatment approach for the treatment of patients with symptomatic carotid stenosis, without causing any harm to the patient, So no ethical approval is needed, and no patient informed consent is required. In recent years, with the continuous advancement of science and technology and new stent materials, intravascular interventional technology has developed rapidly. In continuous clinical practice and research, the safety and effectiveness of stent technology have also been gradually improved. Arterial stenting has gradually become an important method for the treatment of atherosclerotic carotid stenosis. This technique can not only improve the symptoms and prognosis of patients with symptomatic internal carotid stenosis, but also prevent the occurrence of ischemic events. The promotion of this technology has the effect of reducing disability and mortality. The alternative therapy of drug therapy, namely arterial stent implantation, has become a new way to treat atherosclerotic stroke. This treatment technology can quickly relieve the abnormal hemodynamics of distal blood vessels caused by arterial stenosis, which is ischemic. Cerebrovascular disease provides new ideas for treatment. Carotid angioplasty and stenting for symptomatic internal carotid stenosis under a distal cerebral protection device is a safe and effective treatment.